Effects of Tall Fescue Endophyte Type and Dopamine Receptor D2 Genotype on Cow-Calf Performance during Late Gestation and Early Lactation - Sarah A. Wilbanks; Susan Maggie Justice; Thomas West; James L. Klotz; John G. Andrae; Susan K. Duckett (Toxins, 2021)
Grazing endophyte-infected, toxic tall fescue reduces cow/calf production; therefore, this study examines alternate strategies such as use of novel endophyte fescue varieties during late gestation and early lactation or genetic selection of resistant cows. Pregnant cows (n = 75) were randomly assigned to fescue endophyte type: 1) endophyte-infected ergot alkaloid producing tall fescue (E+) or 2) novel endophyte-infected, non-toxic tall fescue (NOV) within maternal (A|A, n = 38 and G|G, n = 37) DRD2 genotype to examine changes in cow/calf performance and milk production during late gestation and early lactation. Grazing E+ fescue pastures during late gestation reduced cow body weight gain but did not alter calf birth weight compared to NOV. Milk production and calf ADG during the first 30 day of lactation were lower for E+ than NOV. The calving rate was reduced, but not calving interval for E+ cows. The adjusted 205-day weight of calves was lower in those grazing E+ with their dams compared to NOV. There were no interactions between DRD2 genotype and fescue endophyte type indicating that genotype was not associated with response to E+ fescue in this study. Overall, grazing NOV tall fescue pastures rather than E+ during critical stages of production improved cow gain during late gestation, calving rate, early milk production and calf growth.